An Analysis of the Paradise Orientation in Maher Zain’s Song 'Jannah' as a Medium for Adolescent Character Education - Faris Akram (Journal of Educational Research and Learning Analytics, 2026)
This study examines the "Heavenly Orientation" in Maher Zain’s song "Jannah" as an innovative medium for adolescent character education. Amidst the persistent crisis of materialism and hedonism among Digital Natives, conventional pedagogical approaches often fail to resonate. Using qualitative content analysis and library research, this research employs systematic close reading to deconstruct the song’s complex lyrical structure. Findings reveal that "Jannah" constructs a transcendental narrative through three dimensions: the transience of worldly life, teleological yearning for the afterlife, and individual moral accountability. These elements function as a spiritual anchor and counter-culture, effectively fostering internal self-regulation rather than simple external compliance. Furthermore, the integration of Learning Analytics offers a modern framework for measuring effectiveness of religious edutainment. This research concludes that "Jannah" serves as a sophisticated pedagogical tool, bridging Islamic theology and contemporary adolescent psychology to foster resilient moral autonomy within the current global digital landscape through the musical fine arts.